Association between psychotropic prescriptions and the total amount of psychotropics ingested during an intentional overdose: A single‐center retrospective study - Iori Tanahashi; Takafumi Shiganami; Takayuki Iwayama; Taisei Wake; Sayaka Kobayashi; Haruo Yoshimasu (Neuropsychopharmacology Reports, 2022)
Abstract Aim To investigate the association between psychotropic prescriptions and the total amount of psychotropics ingested during a subsequent intentional overdose and to examine factors related to the number of psychotropic prescriptions. Methods The initial sample comprised 69 patients who were admitted to the emergency department of a general hospital in Japan following an intentional overdose via psychotropic medications. We performed retrospective hierarchical multiple regression analysis with the total amount of psychotropics ingested at the overdose as a dependent variable and factors related to deliberate self‐harm or overdose identified in previous studies as independent variables. We compared two models, one that did not (Step 1) and one that did (Step 2) include the number of different prescribed psychotropic medications as an independent variable in the analysis. Results Forty‐seven patients were eligible for the analysis. The number of different prescribed psychotropic medications was associated with the total amount of psychotropics ingested at the overdose in Step 2 (β = 0.40, P = .01). There was a trend toward an association between the past number of deliberate self‐harm events and the total amount of psychotropics ingested at the overdose in Step 1 (β = 0.30, P = .05), but this trend was weakened in Step 2 (β = 0.15, P = .33). Conclusion The number of different prescribed psychotropics appeared to influence the risk of subsequent intentional overdose through increasing the total amount of psychotropics ingested. Cumulative psychotropic prescriptions, particularly those delivered after deliberate self‐harm, might be indirectly related to this risk.